CT-guided percutaneous ethanol injection with disposable curved needle for treatment of malignant liver neoplasms and their metastases in retroperitoneal lymph nodes - Zuo, Chang-Jing (World J Gastroenterol, 2004)
AIM: To explore the feasibility of computed tomography (CT)-guided percutaneous ethanol injection (PEI) using a disposable curved needle for treatment of malignant liver neoplasms and their metastases in retroperitoneal lymph nodes. METHODS: CT-guided PEI was conducted using a disposable curved needle in 26 malignant liver tumors smaller than 5 cm in diameter and 5 lymph node metastases of liver cancer in the retroperitoneal space. The disposable curved needle was composed of a straight trocar (21G) and stylet, a disposable curved tip (25 G) and a fine stylet. For the tumors found in deep sites and difficult to reach, or for hepatic masses inaccessible to the injection using a straight needle because of portal vein and bile ducts, the straight trocar was used at first to reach the side of the tumor. Then, the disposable curved needle was used via the trocar. When the needle reached the tumor center, appropriate amount of ethanol was injected. For relatively large malignant liver tumors, multi-point injection was carried out for a better distribution of the ethanol injected throughout the masses. The curved needle was also used for treatment of the metastasis in retroperitoneal lymph nodes blocked by blood vessels and inaccessible by the straight needle. RESULTS: All of the 26 liver tumors received 2 or more times of successful PEI, through which ethanol was distributed throughout the whole tumor mass. Effect of the treatment was monitored by contrast-enhanced multi-phase CT and magnetic resonance imaging (MRI) examinations three months later. Of the 18 lesions whose diameters were smaller than 3 cm, the necrotic change across the whole mass and that in most areas were observed in 15 and 3 tumors, respectively. Among the 8 tumors sizing up to 5 cm, 5 were completely necrotic and 3 largely necrotic. Levels of tumor seromarkers were significantly reduced in some of the cases. In 5 patients with metastases of liver cancer in retroperitoneal lymph nodes who received 1 to 3 times of PEI, all the foci treated were completely necrotic and smaller demonstrated by dynamic contrast-enhanced CT or MRI 3 months later. CONCLUSION: CT-guided PEI using a disposable curved needle is effective, time-saving and convenient, providing an alternative therapy for the treatment of malignant liver tumors and their retroperitoneal lymph node metastases.